Refraction and correction in practice of optometrist - Sever, Anja; Veselý, Petr, 1978 září 14.-; Masarykova univerzita. Katedra optometrie a ortoptiky (2017)
My hypothesis question is regarding “research” on methods which are evaluating the results for prescription in astigmatic values. The important issue for me, by delivered answers in the problem of clients, are how do clients understand the procedure itself, mostly the procedure JCC and within comparison with other method Clock Chart.
Vedoucí práce: Petr Veselý
Diplomová práce (Mgr.)--Masarykova univerzita, Lékařská fakulta, 2017
Keywords: hypermetropie; myopie; refrakční vady; Hyperopia; Myopia; Refractive Errors; diplomové práce; master's theses